Organiczne i próchniczne poziomy gleb jako surowiec w kształtowaniu terenów zieleni = Organic and humus moulds as row material in the development of urban green areas - Greinert, Andrzej; Walczak, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Together with the urban development, one-family-housing estates mainly, there has been an increase in the demand for gardening subsoil. To respond to the arising demand, there has occurred various-sized peat pits in many sites of Lubuskie Region and in the northem part of Lower Silesia. Also turf and sub-turf soil materials are excavated from meadows. Additionally, a material with high organic content is obtained during the construction works, which is removed form the surface of the subsoil as a non-bearing one.
Keywords: 3 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zrównoważona gospodarka zasobami naturalnymi" (24-25.06.2004)